A unified data repository for rich communication services - Sogunle, Oluwasegun Francis (Rhodes University, Faculty of Science, Department of Computer Science, 2017)
Rich Communication Services (RCS) is a framework that defines a set of IP-based services for the delivery of multimedia communications to mobile network subscribers. The framework unifies a set of pre-existing communication services under a single name, and permits network operators to re-use investments in existing network infrastructure, especially the IP Multimedia Subsystem (IMS), which is a core part of a mobile network and also acts as a docking station for RCS services. RCS generates and utilises disparate subscriber data sets during execution, however, it lacks a harmonised repository for the management of such data sets, thus making it difficult to obtain a unified view of heterogeneous subscriber data. This thesis proposes the creation of a unified data repository for RCS which is based on the User Data Convergence (UDC) standard. The standard was proposed by the 3rd Generation Partnership Project (3GPP), a major telecommunications standardisation group. UDC provides an approach for consolidating subscriber data into a single logical repository without adversely affecting existing network infrastructure, such as the IMS. Thus, this thesis details the design and development of a prototypical implementation of a unified repository, named Converged Subscriber Data Repository (CSDR). It adopts a polyglot persistence model for the underlying data store and exposes heterogeneous data through the Open Data Protocol (OData), which is a candidate implementation of the Ud interface defined in the UDC architecture. With the introduction of polyglot persistence, multiple data stores can be used within the CSDR and disparate network data sources can access heterogeneous data sets using OData as a standard communications protocol. As the CSDR persistence model becomes more complex due to the inclusion of more storage technologies, polyglot persistence ensures a consistent conceptual view of these data sets through OData. Importantly, the CSDR prototype was integrated into a popular open-source implementation of the core part of an IMS network known as the Open IMS Core. The successful integration of the prototype demonstrates its ability to manage and expose a consolidated view of heterogeneous subscriber data, which are generated and used by different RCS services deployed within IMS.
Keywords: Uncatalogued